Estimation of sediment production in oil palm expansion areas in the Amazon - Antonio K. L. Silva; Adriano M. L. de Sousa; Joyse T. S. dos Santos; João M. Villela; Lucieta G. Martorano; Silvio Crestana (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Currently, an activity that has become strategic at a national level is the cultivation of oil palm (Elaeis guineensis) in the northeast region of the Pará State, in eastern Brazilian Amazon. However, the impacts of this crop expansion on the hydro-sedimentological cycle are still unknown. Therefore, this study estimated the impacts of oil palm crop expansion on sediment production in a sub-basin under consolidated use of this crop. The Soil and Water Assessment Tool (SWAT) model was applied in the Mariquita sub-basin, calibrated by the flow regionalization technique, using data measured in the field with a current meter. Simulation results indicated an increase in sediment production between the years 2008 and 2013, which can be attributed to the large reduction of areas of secondary vegetation that were replaced by pasture, oil palm and general agriculture. Oil palm areas had a lower average monthly sediment yield in the rainiest period in all simulated years, compared with areas of general agriculture and pasture.